Modeling dynamic weight for 3D navigation routing - Musliman, Ivin Amri; Abdul Rahman, Alias; Coors, Volker (2007)

(untitled)
Currently, most of shortest path algorithm used in GIS application is often not sufficient for efficient management in time-critical applications such as emergency response applications. It doesnâ€™t take into account dynamic emergency information changes at node/vertex level especially when applying in emergency situations such as large fires (in cities or even in buildings), flooding, chemical releases, terrorist attacks, road accidents, etc. In this paper, an approach for finding shortest path or route in a dynamic situation for indoors and outdoors using Single Sink Shortest Path (SSSP) routing algorithm is proposed. This paper discusses the construction of 3D dynamic networks, as well as the corresponding algorithm that can be used for 3D navigation in a 3D GIS environment. The aspect of this research that distinguishes it from other work on the dynamic shortest path problem is its ability to handle â€œmultiple heterogeneous modificationsâ€?: between updates, the input graph is allowed to be restructured by an arbitrary mixture of edge insertions, edge deletions, and edge-length changes. The paper is organized in three general parts. The first part discusses the 3D navigation model, dynamic weight and its functional requirements. The second part presents the 3D dynamic network model and elaborates on the possible solution using SSSP routing algorithm and its implementation. Final discussion on recommendations for future research concludes the paper.